Consequences of circadian disruption in shift workers on chrononutrition and their psychosocial well-being - Azmi N.A.S.M.; Juliana N.; Teng N.I.M.F.; Azmani S.; Das S.; Effendy N. (MDPI AG, 2024)
Indexed by WOS/Scopus/ERA